2017
DOI: 10.3389/fimmu.2017.00437
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Apolipoprotein A-1 IgG Predict All-Cause Mortality and Are Associated with Fc Receptor-Like 3 Polymorphisms

Abstract: BackgroundAutoantibodies against apolipoprotein A-1 (anti-apoA-1 IgG) have emerged as an independent biomarker for cardiovascular disease and mortality. However, their association with all-cause mortality in the community, as well as their genetic determinants, have not been studied.ObjectiveTo determine whether anti-apoA-1 IgG: (a) predict all-cause mortality in the general population and (b) are associated with single-nucleotide polymorphisms (SNPs) in a genome-wide association study (GWAS).MethodsClinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 48 publications
7
60
0
Order By: Relevance
“…In this study, we report, for the first time, that the prevalence of high anti-ApoA-1 IgG levels in children devoid of any concomitant autoimmune diseases is substantial, reaching 38%, and seemed unrelated to familial hypercholesterolemia. Such a prevalence is similar to what has been reported in adults in secondary prevention or equivalent CV risk-associated conditions [4,7,43], and close to double of what has been observed in a general adult population [3], where these antibodies were shown to be associated with a worse overall and CV prognosis [3,5].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we report, for the first time, that the prevalence of high anti-ApoA-1 IgG levels in children devoid of any concomitant autoimmune diseases is substantial, reaching 38%, and seemed unrelated to familial hypercholesterolemia. Such a prevalence is similar to what has been reported in adults in secondary prevention or equivalent CV risk-associated conditions [4,7,43], and close to double of what has been observed in a general adult population [3], where these antibodies were shown to be associated with a worse overall and CV prognosis [3,5].…”
Section: Discussionsupporting
confidence: 85%
“…Among autoantibodies of interest in CVD, the interest in antibodies against apolipoprotein A-1 (anti-ApoA-1 IgG) appears to be gaining momentum. Indeed, three recent studies derived from a large multicenter general population cohort demonstrated that anti-ApoA-1 IgGs were an independent cardiovascular (CV) risk factor predictive of poor prognosis [3][4][5] similarly to what had been reported previously and more recently in high CV risk populations [6][7][8][9][10][11]. In parallel, translational studies pointed to these autoantibodies as mediators of atherogenesis, promoting atherosclerosis, myocardial necrosis, and mice death through toll-like receptors (TLR) 2,4 and CD14 signaling [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The only studies to date to examine the relationships between anti‐ApoA‐I IgG and cardiovascular disease in the general population are based on the large CoLaus study cohort. In this cohort, high anti‐ApoA‐I levels were associated with increased prevalence of existing CVD, defined as myocardial infarction, angina pectoris, coronary interventions, stroke or transient ischaemic attack , and with increased risk for total mortality . In the same study population, Antiochos et al .…”
Section: Discussionmentioning
confidence: 64%
“…The association with receptor-like 3 polymorphisms (a susceptibility gene involved in autoimmune diseases) may suggest an intriguing link between preclinical autoimmunity and mortality risk. 64 Similarly, the association between anti-ApoA-1 IgG and CAD seems to be strongly modulated by polymorphisms of CD14, 65 already recognized as effector of pro-inflammatory response mediated by anti-ApoA-1 IgG. 66 Although preliminary, those data might attract the interest towards the role of preclinical autoimmunity in CV risk.…”
Section: Anti-apoa-1 Igg Serum Levels Predict Worse Poststroke Outcmentioning
confidence: 99%
“…Their levels independently predict both coronary artery disease (CAD) and allcause mortality in the general population. [63][64][65] Noteworthy, genomewide association studies (GWAS) identified two loci potentially involved in the risk associated with anti-ApoA-1 IgG. The association with receptor-like 3 polymorphisms (a susceptibility gene involved in autoimmune diseases) may suggest an intriguing link between preclinical autoimmunity and mortality risk.…”
Section: Anti-apoa-1 Igg Serum Levels Predict Worse Poststroke Outcmentioning
confidence: 99%